T1ρ and T2 relaxation times are associated with progression of hip osteoarthritis. Issue 8 (August 2016) - Gallo, M.C.; Wyatt, C.; Pedoia, V.; Kumar, D.; Lee, S.; Nardo, L.; Link, T.M.; Souza, R.B.; Majumdar, S.
Summary: Objective: To evaluate whether baseline T1ρ and T2 relaxation times of hip cartilage are associated with magnetic resonance imaging (MRI) based progression of hip osteoarthritis (OA) at 18 months. Methods: 3T MRI studies of the hip were obtained at baseline and 18-month follow-up for 54 subjects without evidence of severe OA at baseline [Kellgren–Lawrence (KL) score of 0–3]. 2D fast spin-echo sequences were used for semi-quantitative morphological scoring of cartilage lesions and a combined T1ρ /T2 sequence was used to quantitatively assess cartilage composition. Progression of hip OA was defined based on incident or progression of morphological semi-quantitative grade at 18 months. Baseline T1ρ and T2 relaxation times were compared between progressors and non-progressors using one-way analysis of variance and Mann–Whitney U tests and used to predict progression with binary logistic regression after adjusting for age, gender, body mass index, and KL score. Additionally, a novel voxel-based relaxometry technique was used to compare the spatial distribution of baseline T1ρ and T2 between progressors and non-progressors. Results: Significantly higher baseline T1ρ and T2 values were observed in hip OA progressors compared to non-progressors, particularly in the posterosuperior and anterior aspects of the femoral cartilage. Logistic regression showed that higher baseline T1ρ or T2 values in the femoral cartilage were significantly associated with progression of femoral cartilage lesions at 18 months. Conclusion: T1ρ and T2 relaxation parameters are associated with morphological cartilage degeneration at 18 months and may serve as potential imaging biomarkers for progression of cartilage lesions in hip OA.